Prevention of Postoperative Nausea and Vomiting by Administration of Sub Hypnotic Doses of Propofol and Midazolam during Spinal Anesthesia for Cesarean Section - Saghar Samimi Sade; Fatemeh Davari Tanha; Sara Sadeghi (Tehran University of Medical Sciences, 2010)
Objective: To evaluate, the efficacy of sub hypnotic doses of midazolam and propofol, in prophylactic control of postoperative nausea and vomiting, in parturients undergoing elective cesarean section under spinal anesthesia. Materials and methods: In a double-blind, placebo-controlled, randomized trial, 114 ASA physical status I-II parturient undergoing elective cesarean section under spinal anesthesia (using 0.5% bupivacaine 12 mg) were allocated randomly to receive propofol (20 mg bolus and 1.0 mg/kg/hr infusion, n=38) or midazolam (1 mg bolus and 2.0 mg/hr infusion, n=38) or saline (2 cc IV, n=38) immediately after clamping of umbilical cord. The occurrence of nausea and/or vomiting and respiratory depression was recorded during operation until 12 hr after that. Results: The incidence of nausea and vomiting was significantly lower in midazolam and propofol groups compared with saline group in all 12 hr, (nausea: 19%, 15.8% versus 57.9%), vomiting (7.9%, 5% versus 34.2%). There was not manifestation of respiratory depression at the time of surgery and after it. Conclusion: Sub hypnotic dose of midazolam was as effective as the sub hypnotic dose of propofol for preventing of nausea and vomiting in parturients undergoing cesarean section under spinal anesthesia. We undertook this study in regard to examine a simple, safe and non-expensive antiemetic method.